2014
DOI: 10.1037/a0035837
|View full text |Cite
|
Sign up to set email alerts
|

The distinct role of performing euthanasia on depression and suicide in veterinarians.

Abstract: Veterinarians are more likely to experience mood disorders and suicide than other occupational groups (Fritschi, Morrison, Shirangi & Day, 2009; Platt, Hawton, Simkin, & Mellanby, 2010). The performance of euthanasia has been implicated as contributing determinately to the prevalence of suicide risk and psychological distress in veterinarians (Bartram & Baldwin, 2008, 2010). In contrast, the application of psychological approaches would suggest a possible protective role for euthanasia administration. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
6
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 48 publications
0
56
6
5
Order By: Relevance
“…Frequency of euthanasia demonstrated no significant relationship to psychological distress or compassion fatigue, contrary to other findings in veterinarians and veterinary nurses . Performing euthanasia has been linked to higher work stress and lower job satisfaction not only in veterinarians but also animal care workers from other animal related industries whose role involves performing euthanasia .…”
Section: Discussioncontrasting
confidence: 73%
“…Frequency of euthanasia demonstrated no significant relationship to psychological distress or compassion fatigue, contrary to other findings in veterinarians and veterinary nurses . Performing euthanasia has been linked to higher work stress and lower job satisfaction not only in veterinarians but also animal care workers from other animal related industries whose role involves performing euthanasia .…”
Section: Discussioncontrasting
confidence: 73%
“…Recent assessments of occupational health in veterinarians have consistently demonstrated that adverse outcomes such as high job strain, burnout, depression, and suicide are widespread throughout this profession, and are largely attributed to a combination of both generic and specific occupational stressors (e.g., Tran, Crane & Phillips, ). Although many of the unique aspects of animal caregiving work encountered by veterinarians are also experienced by veterinary nurses, the latter remain a markedly under‐researched professional group with only one known study to date having examined occupational stress in these personnel using an established theoretical explanation of stress (Black, Winefield, & Chur‐Hansen, ).…”
mentioning
confidence: 73%
“…For example, the psychological impact of performing euthanasia to relieve suffering in sick or injured animals is likely to differ as compared with performing euthanasia on healthy or treatable animals for reasons of human convenience. It has been established that euthanasia demands occurring in the latter context are usually opposed to workers’ vocational motivations (i.e., of working within the veterinary field in order to care for animals), and consequently produces a type of ‘moral stress’ commonly experienced as psychological strain (Crane, Bayl‐Smith, & Cartmill, ; Tran et al, ). Anecdotal reports also suggest that veterinary nurses’ continuous exposure to the suffering of animals as a result of ill‐health, injury, advancing age, trauma, abuse, or neglect contributes to significant emotional distress experienced by these personnel (e.g., Ayl, ).…”
mentioning
confidence: 99%
“…For example, euthanasia is part of working as a companion animal veterinarian. Involvement in decisions to end an animal's life can be an acute source of moral and emotional stress for veterinarians . Participants, most notably females in the early stages of training, ranked competency in euthanasia as highly important.…”
Section: Discussionmentioning
confidence: 99%